Characterization and functionalisation of activated carbon for the enhancement of enzyme catalyst activity - Kabbashi, Nassereldeen; Kadouf, Yara; Bello, Ibrahim Adebayo; Mirghani, Mohamed Elwathig Saeed; Musa, Lubna (Elsevier, 2021)
Background and objective: Activated carbon is commonly used as an immobilisation matrix due to its large surface area, making it a highly desirable matrix for use in immobilising enzymes as preparation for use on the industrial scale. The objective of this research is to determine the effectiveness of different acids for functionalisation on immobilisation capacity and also to characterize the functionalized activated carbon for the functional groups present. Materials and methods: Activated carbon was functionalised with three acids (hydrochloric acid, nitric acid and sulphuric acid) along with a control sample washed with distilled water. Immobilisation capacity was calculated with hydrochloric acid functionalized activated carbon (HCl-FAC) giving the highest immobilization capacity (6.022 U/g). Characterisation of the functionalised activated carbon was conducted using FT-IR (Fourier Transform Infra-Red) spectroscopy analysis of the samples with the aim of analyzing the various functional groups present to determine the sample with distinct characteristics thus telling the degree of adsorption of lipase onto the activated carbon powder. Results: HNO3-FAC (functionalized activated carbon) showed a very distinct pattern as a larger number of surface functional groups emerged. The immobilisation on a matrix ensures thermal stability and increased reusability of the enzyme. Therefore, in this research, lipase sourced from Candida antarctica was immobilised on acid functionalised activated carbon. The best acid for functionalisation was found to be hydrochloric acid. Conclusion: Due to the very distinct patterns shown by the FT-IR spectrum of the HNO3-FAC after a fair comparison with others, it allows for a larger number of surface functional groups which will definitely enhance the stability of the enzyme lipase.